A room with a view - Forster, E. M. (Edward Morgan) 1879-1970; Pierce-Roberts, Tony (BBC Video Distributed in the USA and Canada by Warner Home Video, 2003)
Set in the early 1900's. "[The film] tells the story of the coming of age of Lucy Honeychurch (Helena Bonham-Carter). Longing to burst free from the repression of British upper class manners and mores, she must wrestle with her inner romantic longings to choose between the passionate George (Julian Sands) and the priggish but socially suitable Cecil (Daniel Day-Lewis)"--Container.